Demographic and Clinical Characteristics Differentiating Patients Referred for Diagnostic Spirometry and Diagnosed with or without Chronic Obstructive Pulmonary Disease - Flores Uzcanga, Maura Alicia; Narvaez Anzures, Edgar Omar; Jesús, Durán Nah Jaime (British Journal of Healthcare and Medical Research, 2024)
Introduction: Patients who, from the perspective of the family physician, require spirometry to confirm or rule out Chronic Obstructive Pulmonary Disease (COPD) must meet clinical criteria that differentiate them from those who do not appear to need it. Objective: To identify the demographic and clinical characteristics that differentiate patients referred for spirometry during 2022–2023 who were diagnosed with or without COPD. Materials and Methods: This was an observational, retrospective, cross-sectional, and comparative study including 455 patients who underwent spirometry for suspected COPD. This suspicion was based on respiratory data, including three variables—cough, dyspnea, and expectoration—combined into an algorithm. These variables, along with other clinical and demographic data, were compared between patients diagnosed with and without COPD using a logistic regression model (LRM). This model identified, through odds ratios (OR) and 95% confidence intervals (95% CI), the differences between both groups and assessed whether the algorithm influenced the indication to perform spirometry. Results: 29.2% of the patients were diagnosed with COPD through spirometry. The final logistic regression model identified the smoking index as a significant factor, with categories moderate (10 to 20 packs/year, OR 3.88, 95% CI 2.16–6.95), intense (21 to 40, OR 1.95, 95% CI 1.03–3.65), and high (≥ 41, OR 11.54, 95% CI 4.55–29.23). Additionally, the presence of cough (OR 2.18, 95% CI 1.36–3.46) also showed significant differences between patients with and without COPD and influenced the indication to perform spirometry. Conclusions: The smoking index and cough were significantly different factors between patients with and without COPD and influenced the indication to perform pre-diagnostic spirometry. The algorithm, however, did not have a significant impact on this indication.